Politics of Corona Pandemic in Sri Lanka: A Sociological Analysis - Mahees, MTM (Technium Social Sciences Journal, 2021)
The COVID 19 has killed nearly 3.6 million people and around 160 million people have been infected with the virus by end of May 2021 in the world. In the Sri Lankan context, more than 1000 deaths and 150,000 cases have been reported by the end of May 2021. The function of modern society and scientific rationality has been challenged by the pandemic with changes in globalization, the capitalist social order, international affairs, and the modern medicalized systems. On the other hand, the pandemic made an impact on the community, family, and individual life. Moreover, the politics of COVID 19 is very crucial, and it is causing severe impact on the power relation of everyday life of people. This paper attempts to understand the power dynamics operating around the COVID 19 management in Sri Lanka. The main objective of the paper is to make a sociological analysis of the impact of the politics of the corona pandemic on the social life of people in Sri Lanka. The methodology is based on a critical review of relevant literature, content analysis of public views shared by social media (Facebook), and in-depth interviews. Discourse analysis is used to review the literature and other qualitative data. The impact of quarantine regulations on the everyday life of people, marginalization of low-income urban groups, changing power dynamics within the medical and health care systems, ethnicization of COVID 19 and forced cremation of dead bodies, prioritizing military mechanism in combating the pandemic, and ignorance of the involvement of disaster management Institutes are the key discursive findings of the paper. In general, the COVID 19 has made a new mode of bio-politics in Sri Lanka.